Analisis Karakteristik Kebahasaan dan Teknik Penceritaan dalam Memoar Broken Strings Karya Aurelie Moeremans - Nazwa Aidilia Octa Mevia; Claudia Agatha br Tarigan; Triwanti Andini Hutasoit; Jonatan Rio Gultom (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2026)
This study aims to comprehensively analyze the linguistic characteristics and storytelling techniques in the memoir Broken Strings by Aurélie Moeremans. This memoir shares a profound true story of the author's experience surviving emotional manipulation, coercive control, and psychological abuse in a toxic relationship. Using a qualitative descriptive method combining stylistic and structural narratology approaches, this study examines expressive diction, figurative language, and intrinsic narrative elements such as theme, point of view, plot pacing, and characterization. The results show that the author frequently exploits restrictive diction and uses similes and metaphors (such as "cage" and "puppet") to vividly illustrate abstract psychological wounds and trauma into a concrete form. Furthermore, the strict use of a first-person (homodiegetic) point of view combined with the distortion of narrative pacing during traumatic moments proves to be highly effective. This technique successfully replicates the dissociation (freeze) response and immerses the reader in the author's feelings of isolation and internal struggle toward true liberation. The study concludes that the linguistic choices and the application of structural storytelling techniques in this memoir are not merely elements of literary aesthetics, but crucial advocacy instruments in constructing a powerful narrative of trauma and survivor resilienc.